Meteorology and the community - Dixon, F. E. (Statistical and Social Inquiry Society of Ireland, 1957)
Should scientists be subordinate to Civil Servants? Should the scientific services be amalgamated under one Ministry of Applied Science? Is there sufficient liaison between the meteorologists and other scientists, particularly agriculturists, or between the Meteorological Service and the universities? These and similar questions are more often asked than answered, and it is striking that different countries supply very divergent answers. Here is a summary of the replies made in 1950 by 70 States to the question. "Who shall administer the national meteorological service?"
Read before the Society, 1 March 1957
Keywords: Meteorology; Weather and the economy; Irish Meteorological Service; 314.15